2001
DOI: 10.1046/j.1442-2042.2001.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet‐ring cell carcinoma of the urinary bladder inducing renal failure

Abstract: A case of primary signet-ring cell carcinoma of the urinary bladder that was found to have induced renal failure is the second such case reported in the world. Primary signet-ring cell carcinoma of the urinary bladder is a rare histologic variant of adenocarcinoma. The patient died of distant metastasis 8 months after undergoing total cystectomy. The neoplasm had a high stage at diagnosis, so the prognosis was very poor. To improve the prognosis, earlier diagnosis and establishing a regimen of chemotherapy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 8 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…Mucin accumulations form in the cytoplasm and nuclei are unevenly distributed [7]. Routine mucin staining of otherwise normal transitional cell carcinoma will reveal signet ring cells in many cases and the exact percentage of signet ring cells that must be present in order to make the diagnosis of PSRCC of the bladder has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Mucin accumulations form in the cytoplasm and nuclei are unevenly distributed [7]. Routine mucin staining of otherwise normal transitional cell carcinoma will reveal signet ring cells in many cases and the exact percentage of signet ring cells that must be present in order to make the diagnosis of PSRCC of the bladder has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, neoadjuvant chemotherapy followed by cystectomy with lymphadenectomy has become standard care for muscle-invasive blad-der cancer [26] . However, current neoadjuvant chemotherapy or radiotherapy appears not beneficial in SRCC [8] , although intra-arterial platinum or methotrexatebased chemotherapy with or without radiotherapy to control localized disease, with prolonged progressionfree survival, has been reported [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…reported that the serum CEA levels normalized after surgery and increased as the disease progressed. [6] In our case, the serum CEA level was 0 ng/ml.…”
Section: Discussionmentioning
confidence: 55%